Measuring progress on adaptation and mitigation of women in agriculture: What does it take? - Bryan, Elizabeth; Ringler, Claudia (2022)
Elizabeth Bryan and Claudia Ringler November 14, 2022 Food and Agriculture Pavilion COP27, Sharm El-Sheikh